Tips for Building Harmonious School and Community Relations to Improve the Quality of Education - Teguh Waluyo; Sofyan Anif; Sigit Haryanto; Ahmad Muhibbin (Postgraduate, University of Mataram, 2023)
The aim of this research is to describe school tips for building harmonious relationships with the community to improve the quality of education at SD IT Muhammadiyah Pangkalan Kerinci. The research method used is qualitative using data sources in the form of observation, interviews and documentation. Data were analyzed through data reduction, data presentation, and drawing conclusions by checking the validity of the data through triangulation of sources and methods. The research results show that school tips for building harmonious relationships with the community include effective communication, community involvement in school programs, teacher development, increasing student participation, a safe and comfortable learning environment, as well as fairness and transparency. The school creates a conducive climate for parents to actively participate in school activities. Based on the research results, it can be concluded that the school's efforts to improve the quality of education through harmonious relations with the community have been successful by implementing the tips that have been explained. Thus, good cooperation between schools and the community can have a positive impact on improving the quality of education at SD IT Muhammadiyah Pangkalan Kerinci.